2019
DOI: 10.3897/zookeys.846.31944
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyofaunal list of the continental slope of the southern Gulf of Mexico

Abstract: Four oceanographic cruises were carried out between April 2011 and May 2013 on the continental slope of the southern Gulf of Mexico (GoM) in a depth range of 290 to 1200 m on board the R/V JUSTO SIERRA. A total of 91 trawls covered a total swept area of 170.49 hectares. We recorded 177 fish species belonging to 80 families. Fifteen species extended their distribution into the south of the gulf and 37 increased their depth ranges. Five species could have commercial importance: Aphanopuscarbo Lowe, 1839; Hydrola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…In fact, high similarity on the fish species composition of the northern (e.g. McEachran, 2009;Ross et al, 2010;Woodstock, 2018) and southern GoM (San Vicente-Añorve et al, 1998;Ramírez et al, 2019) has been previously suggested. Thus, if we are speaking of a similar fish fauna, it is highly probable that the parasite fauna would also be similar.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, high similarity on the fish species composition of the northern (e.g. McEachran, 2009;Ross et al, 2010;Woodstock, 2018) and southern GoM (San Vicente-Añorve et al, 1998;Ramírez et al, 2019) has been previously suggested. Thus, if we are speaking of a similar fish fauna, it is highly probable that the parasite fauna would also be similar.…”
Section: Discussionmentioning
confidence: 88%
“…Veracruz, no se había reportado a la especie (Schaldach et al 1997). Por otro lado, tal especie no fue registrada en los muestreos de aguas profundas en el golfo de México (Ramírez et al 2019). Por su parte, se revelan registros que corresponden a identificaciones erróneas; así, Ayala-Pérez et al (2015) mencionan a la especie en el sistema estuarino-lagunar de Palizada, Campeche; no obstante, al analizar detalladamente la figura que alude al ejemplar, esta corresponde a un juvenil de Sphoeroides parvus, que se puede reconocer por tener ojos en posición alta, las manchas y lunares de color marrón o gris, principalmente en los costados, y el lunar central de la axila pectoral de coloración menos intensa que el resto de lunares.…”
Section: Discussionunclassified
“…During the scientific expedition COBERPES 5, on board the RV ‘Justo Sierra’, a log was recovered from a trawl (see Ramirez et al ., 2019, for details on sampling method) at 418–427 m depth, off Tabasco, in the Gulf of Mexico. Once on deck, the piece of wood was broken apart and carefully inspected for any wood-associated fauna.…”
Section: Methodsmentioning
confidence: 99%